2017
DOI: 10.4172/2150-3508.1000220
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Changes and Risk Factors of Hepatopancreas Necrosis Disease of Mitten Crab, Eriocheir Sinensis

Abstract: Hepatopancreas necrosis disease (HPND) is a disease and serious impacts on the industry of Chinese mitten crabs (Eriocheir sinensis) culture, however the actual cause of this disease is still not known. In the present study, to explore the pathogenic changes and risk factors caused by HPND, ultrathin sections of different tissues from the diseased crabs were observed with transmission electron microscope. The hepatopancreatic cells, spermatogonium, gill tissues and muscle cells of the diseased crabs showed sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…The Chinese mitten crab ( Eriocheir sinensis ) is one of the important crustaceans with great economic value [ 1 , 2 ]. Crab hepatopancreatic necrosis disease (HPND) had a high mortality rate of about 40–50%, which directly affects the crab farmers [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Chinese mitten crab ( Eriocheir sinensis ) is one of the important crustaceans with great economic value [ 1 , 2 ]. Crab hepatopancreatic necrosis disease (HPND) had a high mortality rate of about 40–50%, which directly affects the crab farmers [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The typical clinical symptoms of crabs with HPND are hepatopancreas degeneration and atrophy, muscle atrophy, and a change in the color of the hepatopancreas from golden to pale yellow and white. The gastrointestinal tract is collapsed, and clear dropsy is observed in the inner cavity of the crab as the disease progresses [ 2 ]. Diseased crabs can survive for a long time, but have no commercial value because of the low content of lipids and proteins and the low growth rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, there was no significant difference in growth performance parameters between any pH groups after 8 weeks, indicating the Chinese mitten crab can survive in pH 6.5-9.5. But there was also a study showing that 40% healthy crabs (about 50 g) died after exposure to pH 9.5 for 2 weeks (Pan et al, 2017). That is because smaller crabs have greater tolerance to environmental stress than bigger ones (Tood and Dehnel, 1960).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HPND symptoms appeared when crabs were cultured in water with a pH of 9.5 to 10, but not when they were cultured in water with different concentrations of avermectin. Therefore, they concluded that HPND in the Chinese mitten crab was not caused by a virus or microsporidian, but caused by water at a high pH or other environmental factors [7]. Shen et al [8] constructed the meta-transcriptomic libraries of the hepatopancreas from crabs with and without HPND, and no significant differences in viral and microsporidial communities were detected.…”
Section: Introductionmentioning
confidence: 99%